2012
DOI: 10.3791/3655
|View full text |Cite
|
Sign up to set email alerts
|

Locked Nucleic Acid Flow Cytometry-fluorescence <em>in situ</em> Hybridization (LNA flow-FISH): A Method for Bacterial Small RNA Detection

Abstract: Fluorescence in situ hybridization (FISH) is a powerful technique that is used to detect and localize specific nucleic acid sequences in the cellular environment. In order to increase throughput, FISH can be combined with flow cytometry (flow-FISH) to enable the detection of targeted nucleic acid sequences in thousands of individual cells. As a result, flow-FISH offers a distinct advantage over lysate/ensemble-based nucleic acid detection methods because each cell is treated as an independent observation, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Fluorescent in situ hybridization (FISH) using DNA probes has long been used to rapidly detect and localize microbial cells in human clinical samples [ 4 , 5 ]. Nonetheless, this method was never employed to detect microorganisms within the human body (or other higher-order animals).…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescent in situ hybridization (FISH) using DNA probes has long been used to rapidly detect and localize microbial cells in human clinical samples [ 4 , 5 ]. Nonetheless, this method was never employed to detect microorganisms within the human body (or other higher-order animals).…”
Section: Introductionmentioning
confidence: 99%
“…Formamide lowers the melting temperature of DNAs by 2.4 -2.9°C/ mole of formamide -with an efficiency depending on the properties of the nucleic acid strands themselves, such as their G+C content, the helix topology and the state of hydration (Blake and Delcourt, 1996). The solvent weakens hydrogen bonds, ultimately allowing lower hybridization temperatures, with similar high stringencies (Casey and Davidson, 1977;Sadhu et al, 1984;Robertson and Vora, 2012). Generally, the more concentrated the formamide, the higher is the stringency of reaction, but it was shown that, similarly to urea, an excess of solvent causes a dramatic drop in probe binding and signal detection (Manz et al, 1992;Bond and Banfield, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…While FISH is conventionally used to study expression in cells or tissues fixed on slides, this technique has also been adapted to study hybridization by flow cytometry (Bauman et al, 1990). A flow cytometry-based technique has been recently used to study gene expression within bacteria and viruses (Robertson et al, 2010;Robertson and Vora, 2012b).…”
Section: Introductionmentioning
confidence: 99%